Two-brightness-amplifier imaging system for energetic-materials-combustion study; Review of Scientific Instruments; Vol. 92, iss. 5 - Gubarev F. A. Fedor Aleksandrovich; Moldabekov A. Abay; Mostovshchikov A. V. Andrey Vladimirovich; Li Lin (2021, 2021)
Title screen